Employment fluctuations and dynamics of the aggregate average wage in Poland 1996 - 2003 - Michał Myck; Leszek Morawski; Jerzy Mycielski (Institute for the Study of Labor (IZA), 2006)
The aggregate average wage is often used as an indicator of economic performance and welfare, and as such often serves as a benchmark for changes in the generosity of public transfers and for wage negotiations. Yet if economies experience a high degree of (nonrandom) fluctuation in employment the composition of the employed population will have a considerable effect on the computed average. In this paper we demonstrate the extent of this problem using data for Poland for the period 1996-2003. During these years employment in Poland fell from 51.2% to 44.2% and most of it occurred between the end of 1998 and the end of 2002. We show that about a quarter of the growth in the average wage during this period could be attributed purely to changes in employment.
urn:nbn:de:101:1-20080702240
Keywords: 330